Leading works in law and social justice - Gordon, Faith; Newman, Daniel (Analysing leading works in law, 2021)
Introduction : law and social justice / Faith Gordon and Daniel Newman -- Lifetimes of commitment to law and social justice / Jacqueline A. Kinghan -- Decolonial violence and the "native intellectual" / Patricia Tuitt -- A very British domination contract? Charles W. Mills' theoretical framework and understanding social justice in Britain / Zara Bain -- Marx and anti-colonialism / Thalia Anthony -- The law of peoples / John Rawls -- Naming 'femicide' / Ashley Rogers -- Feminist legal engagements towards a transformative justice / Jane Krishnadas -- Social justice and the limits of regulation : the enduring insights of Marx's Capital / Steve Tombs -- Mariana Valverde : scale, jurisdiction and social justice / Jess Mant -- Policing the Union's Black : the racial politics of law and order in contemporary Britain / Lambros Fatsis -- Larissa Behrendt - achieving social justice : indigenous rights and Australia's future / Robyn Oxley -- Beyond criminology : taking harm seriously / Lynne Copson -- The souls of black folk, by W.E.B. Du Bois / Bharat Malkani -- At war with the court's 'sublime complacency' : Bob Woffinden remembered / Jon Robins -- The vulnerable subject : anchoring equality in the human condition (Martha Fineman) / Ellen Gordon-Bouvier -- Reflections on law and social justice : Robin West, 'economic man and literary woman' mercer law review / Amir Paz-Fuchs.